Mother’s secure Attachment Style Among Toddlers in Bali - Nice Maylani Asril; Luh Ayu Tirtayani (Mimbar Ilmu, 2023)
Children life will be very dependent on the intensive care provided by the mother. During the child-rearing process, an emotional bond will be established in the interaction between mother and child. The purpose of this study was to explore the parenting styles of mothers for toddlers in Bali. The subjects of this study were 66 mothers with children under five in Bali who came from working mothers, working mothers at home, and housewives, and the sample was determined using a purposive sampling technique. The variables involved in this study, namely: mother's parenting attachment style, mother's employment status, and demographic data of mothers in Bali. This research uses a quantitative descriptive study approach. Data was collected using questionnaires which were distributed using google form and analyzed using quantitative descriptive analysis. The results of this study can explain as many as 66 mothers with children under five, of which 22 people come from mothers who work outside the home with a moderate secure attachment style (the minimum score of secure attachment level is 63, and the maximum score of secure attachment level in this group is 101 ). There were 22 mothers who worked at home, with a minimum score of 71 for secure attachment, and a maximum score of 112 for this group. 22 mothers who did not work with a minimum score of 82 for secure attachment, and a maximum score safe attachment in this group was 118. The results of this study can be used as a development of discussion in parenting science, especially mother's care and attachment.